PERANCANGAN BUKU “27 YEARS LATER; REFORMASI” - Kurnia Setiawan; Alysia Amanda Christianne; Celine Pramana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2026)
The book “27 Years Later; Reformasi” contains the role of 98 reform activists as agents of change that have been recorded from 1998 to 2025. In 2017/2018 the researcher received a grant from the Directorate General of Higher Education, in 2023 and 2024 the research was continued to examine the role of 98 activists in 25 years of reform and during the 2024 presidential election. Based on the 3 studies, it was compiled to be made into a book with the theme of Indonesian change agents. The subjects in the book are activists who are members of the Student Action Front for Reform and Democracy (FAMRED), since they were students until now as leaders in various fields recorded for more than two decades. This book records the experiences, life values, and challenges faced by post-reform activists in maintaining the spirit of change amidst various political and social situations, especially before and after the 2024 presidential election. The research was conducted using Anthony Giddens' structuration approach to understand the dialectical interaction between agents (activists) and social structures in the process of social change. Based on the studies conducted, some activists are influenced by existing structure/ reproducing the structure and some actively change these structures in an effort to achieve their personal goals or reformation goals. The design of the book follows the Five phases of graphic design from Robin Landa: orientation, analysis, concept, design, implementation. Through this book, the history of the 98 reforms is recorded based on the results of ongoing research so that it is hoped that it can provide insight into the transformation process of reform movement activists, while reflecting the relevance of the struggle in the current context. ABSTRAK Buku “27 Years Later; Reformasi” berisi tentang peran aktivis reformasi 98 sebagai agen perubahan yang telah direkam sejak tahun 1998 hingga 2025. Pada tahun 2017/2018, peneliti telah mendapatkan hibah Dikti. Pada tahun 2023 dan 2024, penelitian dilanjutkan untuk mengkaji peran aktivis 98 dalam 25 tahun reformasi dan pada saat pemilihan presiden 2024. Berdasarkan 3 penelitian tersebut, diramu menjadi buku bertema agen perubahan Indonesia. Subjek dalam buku adalah para aktivis yang tergabung dalam organ Front Aksi Mahasiswa untuk Reformasi dan Demokrasi (FAMRED), sejak mereka masih mahasiswa sampai saat ini, yang menjadi pemimpin di berbagai bidang yang direkam selama lebih dari dua dekade. Buku ini merekam pengalaman, nilai-nilai hidup, serta tantangan yang dihadapi aktivis pasca-reformasi dalam mempertahankan semangat perubahan di tengah berbagai suasana politik dan sosial, khususnya menjelang dan pasca pemilihan presiden 2024. Penelitian ini menggunakan pendekatan strukturasi Anthony Giddens untuk memahami interaksi dialektis antara agen (aktivis) dan struktur sosial dalam proses perubahan sosial. Berdasarkan kajian yang dilakukan, para aktivis ada yang dipengaruhi/mereproduksi struktur yang ada dan ada pula yang secara aktif memperbaiki/mengubah struktur yang ada dalam upaya mencapai tujuan pribadinya ataupun tujuan reformasi. Perancangan buku mengikuti tahapan “Five phases of graphic design” dari Robin Landa: orientation, analysis, concept, design, implementation. Melalui buku ini, sejarah reformasi 98 direkam berdasarkan hasil penelitian yang berkelanjutan sehingga diharapkan dapat memberikan wawasan mengenai proses transformasi para aktivis gerakan reformasi, sekaligus merefleksikan relevansi perjuangan tersebut dalam konteks kekinian.